New species of Lanonia, Licuala, and Pinanga (Arecaceae) from Vietnam - Henderson, Andrew; Dung, Nguyen Quoc (Phytotaxa, 2017)
Four new species of Lanonia, six of Licuala, and one of Pinanga (Arecaceae) are described and illustrated and compared with similar species. One species in Licuala is transferred to Lanonia.